Analytical sensitivity and clinical performance of a triplex RT-qPCR assay using CDC N1, N2, and RP targets for SARS-CoV-2 diagnosis - Freire-Paspuel, Byron (Int J Infect Dis, 2021)
BACKGROUND: Several RT-qPCR kits are available for SARS-CoV-2 diagnosis and some have emergency use authorization from the US Food and Drug Administration. In particular, the nCoV19 CDC kit includes two targets for detecting SARS-CoV-2 (N1 and N2) and an RNaseP (RP) target for RNA extraction quality control, all of which are labeled with FAM, and thus three PCR reactions are required per sample. METHODS: We designed a triplex RT-qPCR assay based on nCoV19 primers and probes where N1, N2, and RP are labeled with FAM, HEX, and Cy5, respectively, so only a single PCR reaction is required for each sample for SARS-CoV-2 diagnosis. RESULTS: In total, 172 samples were analyzed in both singleplex and triplex assays, where 86 samples tested SARS-CoV-2 negative with both assays, so the triplex assay specificity was 100%. In addition, 86 samples tested SARS-Co-V 2 positive with the singleplex assay and 84 with the triplex assay, so the sensitivity was 97.7%. The limit of detection for the triplex assay was determined as 1000 copies/mL. CONCLUSIONS: This new triplex RT-qPCR assay based on primers and probes from the CDC protocol is highly reliable for SARS-CoV-2 diagnosis, and it could speed up detection and save reagents during the current SARS-CoV-2 testing supplies shortage.